Coherence, not conditional meaning, accounts for the relevance effect - Bourlier, Maxime; Jacquet, Baptiste; Lassiter, Daniel; Baratgin, Jean (Frontiers in Psychology, 2023)
Missing-link conditionals like “If bats have wings, Paris is in France” are generally felt to be unacceptable even though both clauses are true. According to the Hypothetical Inferential Theory, this is explained by a conventional requirement of an inferential connection between conditional clauses. Bayesian theorists have denied the need for such a requirement, appealing instead to a requirement of discourse coherence that extends to all ways of connecting clauses. Our experiment compared conditionals (“If A, C”), conjunctions (“A and C”), and bare juxtapositions (“A. C.”). With one systematic exception that is predicted by prior work in coherence theory, the presence or absence of an inferential link affected conditionals and other statement types in the same way. This is as expected according to the Bayesian approach together with a general theory of discourse coherence.